2013
DOI: 10.4161/cc.27523
|View full text |Cite|
|
Sign up to set email alerts
|

SIRT1 is upregulated in cutaneous T-cell lymphoma, and its inhibition induces growth arrest and apoptosis

Abstract: Silent information regulator type-1 (SIRT1) is the best-studied member of the Sirtuin (Sir2) family of nicotinamide dinucleotide (NAD)-dependent class III histone deacetylases (HDACs), but has not yet been explored in cutaneous T-cell lymphoma (CTCL). We analyzed five CTCL cell lines and lesional tissues using flow cytometry, immunostaining, immunoblotting, cell death, viability, and apoptosis assays, small-molecule inhibitors, and shRNA knockdown. We found strong SIRT1 expression among CTCL lines relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…In 3 CTCL cell lines, TOX suppression by lentivirus-mediated shRNA gene silencing markedly normalized the CTCL cells' resistance to apoptosis and abnormal cell cycle progression, the 2 best-characterized features of CTCL cells. [5][6][7][8] In agreement with in vitro data, subcutaneous injection of CTCL cells into NSG mice confirmed this proliferative disadvantage, in that the ability of TOX-suppressed CTCL cells to induce local tumors was significantly impaired or even abolished. In aggregate, these findings demonstrate the biological importance of sustained TOX activation to the leukemic activities of CTCL cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In 3 CTCL cell lines, TOX suppression by lentivirus-mediated shRNA gene silencing markedly normalized the CTCL cells' resistance to apoptosis and abnormal cell cycle progression, the 2 best-characterized features of CTCL cells. [5][6][7][8] In agreement with in vitro data, subcutaneous injection of CTCL cells into NSG mice confirmed this proliferative disadvantage, in that the ability of TOX-suppressed CTCL cells to induce local tumors was significantly impaired or even abolished. In aggregate, these findings demonstrate the biological importance of sustained TOX activation to the leukemic activities of CTCL cells.…”
Section: Discussionsupporting
confidence: 81%
“…Although the etiology of CTCL is not yet clear, accumulating evidence indicates that defects in apoptosis and cell cycle control are critical in disease pathogenesis. [5][6][7][8] However, the molecular events leading to these abnormalities have not been well understood. By transcriptome analysis, we have recently demonstrated that the transcript levels of thymocyte selection-associated high-mobility group (HMG) box gene (TOX) are abnormally increased in early-stage MF skin biopsy specimens but not in the biopsy specimens of benign inflammatory dermatoses (BID) or normal skin.…”
Section: Cd45romentioning
confidence: 99%
“…Previous studies have shown that SIRT1 promotes cell survival by repressing p53-dependent apoptosis in response to DNA damage and oxidative stress. This repression occurs via physical interaction with both p53 and the forkhead transcription factor (FOXO) family of proteins (28)(29)(30). Additionally, evidence suggests that SIRT1 may be involved in pathways of telomere maintenance, giving them a putative role in aging and survival (31).…”
Section: Introductionmentioning
confidence: 99%
“…49 Recent findings showed that the class III HDAC, SIRT1, is overexpressed in CTCL and that its knock-down or inhibition induced growth arrest and apoptosis. 50 31 MTX and PDX are metabolized intracellularly into polyglutamates by folylpolyglutamyl synthetase. 16,32 These polyglutamates are preferentially retained in cells, thereby making them less susceptible to efflux-based drug resistance.…”
Section: Hdacmentioning
confidence: 99%